Evaluación de tres tipos de abonos complementando la aplicación de ácidos húmicos en el cultivo de tomate riñón (Lycopersicum esculentum Mill) bajo invernadero en el Cantón Ibarra - Herrera Ortega, Beatriz Yolanda (2018)
7. SUMMARY This research was conducted in the Florida area called Canton Ibarra; where the application of three types of organic fertilizers was evaluated, the same as were Humus, compost and Bocashi (3000 kg / ha), complemented with humic acids in three doses(1000, 2000 and 3000 cc / ha), in the handling and production of tomato kidney (M. Licopersicum esculentum) under greenhouse; their advantage and performance was evaluated in the culture; Regarding the work methodology Design Randomized Complete (DBCA) blocks are implemented; determining variables to evaluate how plant height, stem diameter 30, 60 and 90 DDT, number of flowers at 60 DDT, number of fruits to 80 DDT, equatorial diameter, polar and weight to 90 DDT and performance . The results were the best dose corresponds to T7 composed of humus in doses of 3000 kg / ha more 3000cc humic acid / ha, reaching the best results: For plant height have 30, 60 and 90 DDT, whose averages were 72.57 cm, 185.17 cm and 301.62 cm, respectively; for the variable diameter of stem 30, 60 and 90 DDT, the following averages, 6.07 cm, 10.33 cm and 20.67 cm, respectively, at 60 DDT, the variable number of flowers per plant was made, taking an average of 40.67 flowers / pl were obtained; to 80 DDT number of fruits it was taken, which averaged 34.67 fruits / pl; the polar and equatorial diameter of the fruit, also took 90 DDT, with an average of 8.67 cm and 9.17 cm, respectively; for fruit weight average 182, 33 g was taken; these data we proceeded to calculate yield, having an average of 20, 07 TM / ha; Finally, the economic analysis was performed, taking an economic utility of 11356 USD / ha. Is recommended to tomato crop kidney (Licopersicum sculentun M) 3000 kg / ha of húmus, accompanied 3000 cc of humic acids, and this treatment proved to be the best in research.